DEMNITATEA UMANĂ ÎN CONTEXTUL SOCIETĂȚII POSTMODERNE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Human Dignity in the Context of Postmodern SocietyIt was a time when the human dignity in the society was lower and religious liberty had been related with the king and priests power. As the historical epochs pass by some change took place but the problem of human dignity still remains. Today, the globalization of the society put the things back like in old times. The peoples who are in power establish the principles that guide the position of human dignity and religion liberty. We need a certain reference system and the principles that lead the society to be correspondences and coherences. It is only one true reference systems establish by God. He is the only one who could really define what is good and what is wrong.